IMPLEMENTASI TRI HITA KARANA SEBAGAI STRATEGI PARIWISATA BALI BERBASIS ENVIRONMENTAL SECURITY - I Putu Arya Aditia Utama; Muhammad Yamin (Review of International Relations, 2022)
As a tourism area that has been worldwide, Bali certainly has various problems it faces. The rapid development of tourism in Bali has resulted in many impacts resulting from this industry. The impacts resulting from the tourism industry not only provide benefits for Bali, but also provide considerable losses. One of the aspects that suffer the most from the development of tourism is the environmental aspect. As a multidimensional industry, tourism will have many significant impacts on the environment, starting from the construction of facilities, the use of transportation equipment, and the operation of the tourism industry. Therefore, Bali must prevent any damage that may be caused by the tourism industry because Bali also offers natural beauty as a tourism attraction. The ideal strategy that can be applied by Bali is to implement the Tri Hita Karana concept which consists of parayangan, pawongan, and palemahan. The implementation of the Parahyangan can be done by protecting the environment around the temple which is also a tourist destination. The implementation of pawongan is carried out by collective action between the community, government, and tourism actors to jointly realize tourism based on environmental security. The application of palemahan can be done starting from small actions, namely not littering and being able to protect the environment properly. The application of the three elements that compose Tri Hita Karana will be able to create Bali tourism based on environmental security and be able to overcome various problems that threaten the environment.